1997
DOI: 10.1016/s0885-3924(97)00010-9
|View full text |Cite
|
Sign up to set email alerts
|

Cancer pain education among family physicians

Abstract: This study used performance-based testing (objective structured clinical evaluation, OSCE) to evaluate the skills of family physicians in assessing and managing the severe pain of a cancer patient, and evaluated a new method of education about the management of cancer pain. Twenty-four primary care physicians completed a detailed pain assessment of the same standardized cancer pain patient (Part A). A proctor observed the interviews and rated the physicians on a variety of pre-determined items believed to be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
1
17
1
1
Order By: Relevance
“…16 This finding is similar to the study by Sloan in US where 70% of the physicians were able to assess pain correctly. 6 In the first case scenario on severe pain, the study results reflect a similar rate of morphine use as in the Canadian study 17 compared with other studies conducted in the US and Canada by Cleeland 18 and Macdonald, 19 where only 41% and 48% of the doctors, respectively, would select a strong opioid as the initial management of severe cancer pain. In our study, although a strong opioid was selected by a large proportion of the doctors, co-analgesicwas rarely selected.…”
Section: Choice Of Analgesicsupporting
confidence: 72%
See 1 more Smart Citation
“…16 This finding is similar to the study by Sloan in US where 70% of the physicians were able to assess pain correctly. 6 In the first case scenario on severe pain, the study results reflect a similar rate of morphine use as in the Canadian study 17 compared with other studies conducted in the US and Canada by Cleeland 18 and Macdonald, 19 where only 41% and 48% of the doctors, respectively, would select a strong opioid as the initial management of severe cancer pain. In our study, although a strong opioid was selected by a large proportion of the doctors, co-analgesicwas rarely selected.…”
Section: Choice Of Analgesicsupporting
confidence: 72%
“…3 Several factors have been identified to explain the undertreatment of cancer pain. Many sur-veys have demonstrated that physicians' knowledge about cancer pain is deficient, 4,5 partly because physicians are inadequately trained in cancer pain management 6 and that they are overly concerned about the addictive effects of analgesics. 4 The lack of expertise has been related to inadequate training both at the undergraduate and post graduate levels.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers' found that hospice nurses completed items related to pain intensity, pain location and relieving factors very well and did well in relation to analgesic recommendations. They conclude that hospice nurses' performance in both cancer pain assessment and management recommendations exceeded that of resident house staff and family physicians (Sloan et al, 1997). The researchers therefore make the comparison between hospice nurses' skills in pain assessment and management and those of less specialist medical staff.…”
Section: Situating Specialist Palliative Care Nurse Expertisementioning
confidence: 99%
“…1,2 Despite substantial evidence that pain can be managed effectively in as many as 90% of patients, inadequate relief remains a significant problem. Many sur-veys have demonstrated that physicians' knowledge about cancer pain is deficient, 4,5 partly because physicians are inadequately trained in cancer pain management 6 and that they are overly concerned about the addictive effects of analgesics. Many sur-veys have demonstrated that physicians' knowledge about cancer pain is deficient, 4,5 partly because physicians are inadequately trained in cancer pain management 6 and that they are overly concerned about the addictive effects of analgesics.…”
Section: Introductionmentioning
confidence: 99%